Seizure activity triggers tau hyperphosphorylation and amyloidogenic pathways. Issue 4 (28th February 2022) - Canet, Geoffrey; Zub, Emma; Zussy, Charleine; Hernandez, Célia; Blaquiere, Marine; Garcia, Valentin; Vitalis, Mathieu; deBock, Frederic; Moreno‐Montano, Maria; Audinat, Etienne; Desrumaux, Catherine; Planel, Emmanuel; et al.
Abstract: Objective: Although epilepsies and neurodegenerative disorders show pathophysiological similarities, their direct functional associations are unclear. Here, we tested the hypothesis that experimental seizures can induce tau hyperphosphorylation and amyloidogenic modifications over time, with intersections with neuroinflammation. Methods: We used a model of mesial temporal lobe epilepsy (MTLE) where unilateral intrahippocampal injection of kainic acid (KA) in C57BL/6 mice elicits epileptogenesis and spontaneous focal seizures. We used a model of generalized status epilepticus (SE) obtained by intraperitoneal KA injection in C57BL/6 mice. We performed analyses and cross‐comparisons according to a schedule of 72 h, 1 week, and 8 weeks after KA injection. Results: In experimental MTLE, we show AT100, PHF1, and CP13 tau hyperphosphorylation during epileptogenesis (72 h–1 week) and long‐term (8 weeks) during spontaneous seizures in the ipsilateral hippocampi, the epileptogenic zone. These pathological modifications extended to the contralateral hippocampus, a seizure propagating zone with no histological lesion or sclerosis. Two kinases, Cdk5 and GSK3β, implicated in the pathological phosphorylation of tau, were activated. In this MTLE model, the induction of the amyloidogenic pathway (APP, C99, BACE1) was prominent and long‐lasting in the epileptogenic zone. These Alzheimer's disease (AD)‐relevant markers, established during seizure progression and recurrence, reciprocated an enduring glial (GFAP, Iba1) inflammation and the inadequate activation of the endogenous, anti‐inflammatory, glucocorticoid receptor system. By contrast, a generalized SE episode provoked a predominantly transient induction of tau hyperphosphorylation and amyloidogenic markers in the hippocampus, along with resolving inflammation. Finally, we identified overlapping profiles of long‐term hippocampal tau hyperphosphorylation by comparing MTLE to J20 mice, the latter a model relevant to AD. Significance: MTLE and a generalized SE prompt persistent and varying tau hyperphosphorylation or amyloidogenic modifications in the hippocampus. In MTLE, an AD‐relevant molecular trajectory intertwines with neuroinflammation, spatiotemporally involving epileptogenic and nonlesional seizure propagating zones.